Implementation and evaluation of a National External Quality Control Program for Cervical Cytology in Mexico - Flisser Ana; García-Malo Felipe; Canepa María de los Angeles; Doncel Susana; Espinoza Raquel; Moreno Ramiro; Avila Isidro; Pérez-Palacios Gregorio; Tapia-Conyer Roberto; de la Fuente Juan Ramón (Instituto Nacional de Salud Pública, 2002)
Objective. To evaluate cytology laboratories and the performance of cytotechnologists for establishing efficient external quality control for Mexico's National Program for the Prevention and Control of Cervical Cancer. Material and Methods. During January and February 1998, an on-site evaluation of all cytology laboratories of the Ministry of Health found that only 70% of the microscopes were in adequate working conditions, reagents were out of date, and working conditions were sub-optimal. A program for external quality control based on proficiency testing was established for cytotechnologists. Fifty slide sets with 20 Papanicolaou slides and 10 photographic slides were prepared. The sets were given to the cytotechnologists for evaluation and again one year later by courier. Results. Twenty-one percent of microscopes were repaired and 9% replaced; reagents were distributed and laboratory facilities improved. Only 16% of cytotechnologists passed the initial proficiency test. Cytotechnologists received a refresher training course: one year later 67% of them passed the proficiency test. To ascertain that each slide was correctly diagnosed, 41 sets were rescreened by expert cytopathologists or cytologists and their diagnoses compared to the original ones. Thirty-seven sets had 86% to 96% concordance. Conclusions. This new system for external quality control of cervical cytology allowed the opportune and reliable evaluation of the performance of cytotechnologists.